2022
DOI: 10.5435/jaaosglobal-d-21-00092
|View full text |Cite
|
Sign up to set email alerts
|

Timeout? The Epidemiology of Pediatric Sports Injuries During the COVID-19 Pandemic

Abstract: Background: The COVID-19 pandemic resulted in closure of schools and playgrounds while requiring social distancing, changes that likely affected youth sports participation. The purpose of this study was to identify changes in the epidemiology of pediatric sports injuries during the COVID-19 pandemic. Methods: This retrospective cohort study included patients between the ages of 4 and 18 years who presented to orthopaedic clinics within a single children's hospital network with an acute injury sustained during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Significant trends found in our study included the decrease in relative frequency of sprains/strains and the increase in relative fracture frequency in both 2020 and 2021. A study by Wild et al 31 also revealed a higher proportion of orthopaedic sports injuries to be fractures in 2020. Baxter et al 4 found a 108.4% increase in proportion of supracondylar fractures presenting to clinic during lockdown when compared with 2019.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Significant trends found in our study included the decrease in relative frequency of sprains/strains and the increase in relative fracture frequency in both 2020 and 2021. A study by Wild et al 31 also revealed a higher proportion of orthopaedic sports injuries to be fractures in 2020. Baxter et al 4 found a 108.4% increase in proportion of supracondylar fractures presenting to clinic during lockdown when compared with 2019.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have investigated the change in pediatric emergency room and outpatient visits for trauma, sport, and non–sport related injuries due to the COVID-19 pandemic. 22,24,31 Pines et al 22 found that there was a 67% decrease in non–COVID-19 emergency room visits from March to April 2020 for individuals 14 to 17 years of age compared with the same time period in 2019. 22 A study investigating outpatient orthopaedic clinics from a single children’s hospital network revealed that 15.2% of the injuries treated from March to June 2020 were sustained in a formal sports setting, compared with 71.4% in 2018 and 2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in sport-related concussion and TBI claims in New Zealand during the COVID-19 pandemic is consistent with observed decreases in the incidence of sport-related injuries in other countries. 15 , 16 , 17 For instance, studies have demonstrated that lockdowns and restrictions related to the COVID-19 pandemic resulted in significant declines in sport-related injuries presenting to Emergency Departments and level 1 paediatric trauma hospitals in the United States. 15 , 16 There were also fewer sport-related injuries seen in outpatient settings during the COVID-19 pandemic, and most of these injuries occurred outside of organised sports settings.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 There were also fewer sport-related injuries seen in outpatient settings during the COVID-19 pandemic, and most of these injuries occurred outside of organised sports settings. 17 Naturally, the magnitude of the reduction in incidence varies depending on the level and duration of government-imposed restrictions across countries and regions. In New Zealand, alert level 3 or 4 was imposed for 14 % and 6 % of 2020 and 2021, respectively, whilst the estimated reductions in sport-related concussion and TBI claims were 30 % and 10 % for 2020 and 2021, respectively.…”
Section: Discussionmentioning
confidence: 99%